Pengaruh fase bulan terhadap produktivitas hasil tangkapan bagan apung di perairan teluk Mutiara Kabupaten Alor - Efrin Antonia Dollu; Angriani P. H. Dasing; Yulianto Tell (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2023)
Bagan Apung fishing gear is one of the fishing gear that uses light as a tool in the fishing process. Floating Bagan fishing gear is a fishing gear that produces a high enough value for fishery production. The value of marine fishery production sometimes experiences instability which can be caused by several factors including oceanographic, weather or climate factors and the period of the moon phase. The research method used in this study was observation or following the fishing operation directly on Bagan Apung as many as 16 trips. Data analysis was carried out to see the effect of the catch on the moon phase using the t test and the BNT follow-up test. The composition of the catch shows that the crescent phase has a catch composition of 33% or with a total catch of 884 kg. The first bright spring moon phase with a catch composition of 17% or with a total catch of 454 kg, the full moon phase with a composition of 13% or with a total catch of 346 kg. The second semi-bright moon phase with a composition of 37% or with a total catch of 987 kg. The results of the t test and further test (BNT) showed that there was a moon phase on the catch of Bagan Apung.